2014
DOI: 10.1590/s1517-83822014000300047
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus surveillance among young children in São Paulo, Brazil: the impact of vaccination

Abstract: This study assessed the presence of influenza virus among young children and the coverage of vaccination from 2010 to 2012 in São Paulo, Brazil. Our results demonstrated a lower rate of influenza detection and a predominance of influenza B. A decrease of coverage vaccination through the surveillance periods was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the above-described study, the highest rate of infection was observed among those was reported in a study among young children. 19 However, considering that information regarding the time of vaccination was not available, these patients could have been recently vaccinated and, therefore, did not reached the adequate protective antibody titers, which are acquired at least 2 weeks postvaccination. Nonetheless, all vaccinated patients were not later hospitalized, which could point to some immunization protection.…”
Section: Discussionmentioning
confidence: 99%
“…In the above-described study, the highest rate of infection was observed among those was reported in a study among young children. 19 However, considering that information regarding the time of vaccination was not available, these patients could have been recently vaccinated and, therefore, did not reached the adequate protective antibody titers, which are acquired at least 2 weeks postvaccination. Nonetheless, all vaccinated patients were not later hospitalized, which could point to some immunization protection.…”
Section: Discussionmentioning
confidence: 99%